Impact of inclusive leadership on innovative work behavior: The role of psychological safety. (23rd February 2017) - Javed, Basharat; Naqvi, Sayyed Muhammad Mehdi Raza; Khan, Abdul Karim; Arjoon, Surendra; Tayyeb, Hafiz Habib
Abstract: The purpose of this study is to examine inclusive leadership as a predictor of innovative work behavior with the mediating role of psychological safety. Data were collected from supervisors–subordinates dyads working in textile industry in Pakistan. Our findings suggest that inclusive leadership is a positively related with innovative work behavior, and psychological safety mediates the effect of inclusive leadership on innovative work behavior. The leader–member exchange theory was used to build our theoretical model. We have also discussed theoretical and practical implications of our findings.